2020
DOI: 10.18410/jebmh/2020/609
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Practices among Rural High School Students in Thrissur - Central Kerala

Abstract: BACKGROUND Adolescence is the transitional phase of growth and development between childhood and adulthood. Menstruation, which is a milestone event in a girl's reproductive life begins during this period and it is also one of the major causes of stress in this stage. Adequate knowledge and good menstrual practices can help in addressing this stress and also in preventing reproductive tract infections to a great extent. This study tries to assess the awareness with regard to menstrual practice and its determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A study done in Kerala among menstrual cup users found that majority didn't faced any side effects. 5,13 They found 0.5% had allergy, 1% rashes, 2.5% faced dryness, and 2% suffered from infection. They also noted that, 46.9% felt uncomfortable during their first use of menstrual cup and in subsequent use, only 1.9% felt it to be uncomfortable.…”
Section: Discussionmentioning
confidence: 97%
“…A study done in Kerala among menstrual cup users found that majority didn't faced any side effects. 5,13 They found 0.5% had allergy, 1% rashes, 2.5% faced dryness, and 2% suffered from infection. They also noted that, 46.9% felt uncomfortable during their first use of menstrual cup and in subsequent use, only 1.9% felt it to be uncomfortable.…”
Section: Discussionmentioning
confidence: 97%